2021
DOI: 10.1017/jns.2021.58
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adverse birth outcomes among pregnant adolescents in Ashanti Region, Ghana

Abstract: Adolescent pregnancy is associated with adverse birth outcomes. However, the determinants of these outcomes are understudied. The present study sought to identify the predictors of adverse birth outcomes among pregnant adolescents in Ghana. In this prospective health centre-based study, 416 pregnant adolescents, aged 13–19 years old, were followed, and 270 birth outcomes were evaluated. We collected data on socio-demographic variables, eating behaviour, household hunger scale (HHS), lived poverty index (LPI) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Nevertheless, this study used two GWAS databases and lacked individual data to allow subgroup analysis by age or sex; thus, any potential nonlinear relationships or stratification effects by health status, age, or sex cannot be examined. Second, we only adjusted for BMI and alcohol consumption in the multivariable MR analysis, and some factors, such as age and gestational age, may confuse the association between education and birth weight ( Mohammed et al, 2019 ; Jeena et al, 2020 ; Annan et al, 2021 ). If possible, studies should continue to explore other confounding factors to fully understand the relationship between education and birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this study used two GWAS databases and lacked individual data to allow subgroup analysis by age or sex; thus, any potential nonlinear relationships or stratification effects by health status, age, or sex cannot be examined. Second, we only adjusted for BMI and alcohol consumption in the multivariable MR analysis, and some factors, such as age and gestational age, may confuse the association between education and birth weight ( Mohammed et al, 2019 ; Jeena et al, 2020 ; Annan et al, 2021 ). If possible, studies should continue to explore other confounding factors to fully understand the relationship between education and birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 20% of adolescents from low and middle-income countries give birth [ 1 , 2 ]. They have a higher frequency of adverse outcomes such as preterm birth, small-for-gestational-age (SGA), and increased neonatal and maternal mortality risk than pregnant adults [ 3 , 4 , 5 ]. Gestational weight gain (GWG) has been associated with both short-term and long-term consequences, such as anemia and preeclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…While our study focused only on the role of vaginal inflammation, it is crucial to acknowledge the potential contribution of other factors in the complex relationship between vaginal sexual behavior and birth outcomes. For example, previous research has suggested that factors such as short cervical length [59,60], poor nutritional status [61], higher parity [62,63], and lower socioeconomic status [64] could impact birth outcomes. Health benefits of vaginal sexual activity on a wide range of medical and psychological measurements have also been reported [65].…”
Section: Discussionmentioning
confidence: 99%